Great American city: Chicago and the enduring neighborhood effect - Sampson, Robert J. (The University of Chicago Press, 2024)
"In his magisterial Great American City, Robert J. Sampson puts social scientific data behind an argument that we all feel and experience everyday: the neighborhood you live in has a big effect on your life and the city you live in. Not only does your neighborhood determine where your nearest hospital is, what kind of schools your children can attend, or how many police officers you might encounter (and how they respond to you), it affects how you feel, how you think about the world and your place in it. Like many sociologists before him, Sampson looks to Chicago to make his insightful interventions, based on extensive data collected across the city's diverse neighborhoods. This edition includes a new afterword by Sampson reflecting on changes in Chicago and the country that have occurred since the book was initially published. He notes the increase in gun violence, both among civilians and police killings of civilians, as well as steady or growing rates of segregation despite an increase in diversity. With these changes have come new research, much of it a continuation or elaboration of the work in Great American City. He updates readers on the status of the research initiative that serves as the basis of Great American City, the Project on Human Development in Chicago Neighborhoods (PHDCN), and summarizes how scholars have taken up his work. Many of these scholars have new tools at their disposal with the rise of big data; Sampson remarks on these changes in the field"--